2000
DOI: 10.1263/jbb.90.681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on Transesterification Activity of Rhizopus chinensis Lipase.

Abstract: The transesterification activity of powder lipase prepared from the purified lipase of Rhizopus chinensis cells by freeze-drying was quite low compared with that of acetone-dried cells. Additives which could enhance the transesterification activity of the freeze-dried powder lipase were screened. The freeze-dried lipases prepared with certain fatty acid methylesters or certain types of surfactants exhibited high transesterification activity. It was shown that not only the solubility of the freeze-dried lipase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Fatty acid methyl esters of which the number of carbon atoms in the chain were 6, 14, and 18 exhibited good results. [3] According to the present work the transesterification activities of the immobilized lipase prepared with the GA-C6, GA-C14 and GA-C18 particles were high. These results agreed with those obtained in the screening.…”
Section: Transesterification Reaction Catalyzed By Immobilized Lipasesupporting
confidence: 60%
See 1 more Smart Citation
“…Fatty acid methyl esters of which the number of carbon atoms in the chain were 6, 14, and 18 exhibited good results. [3] According to the present work the transesterification activities of the immobilized lipase prepared with the GA-C6, GA-C14 and GA-C18 particles were high. These results agreed with those obtained in the screening.…”
Section: Transesterification Reaction Catalyzed By Immobilized Lipasesupporting
confidence: 60%
“…In our previous article, [3] the transesterification activity of a freeze-dried lipase, which was prepared from Rhizopus chinensis lipase in the presence of a fatty acid methylester or tert-octylphenoxy polyethoxy ethanol (Triton X-100), was considerably high compared to that prepared without additives. This result suggested that these additives improved the solubility and stability of the lipase in nonaqueous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the treatment of lipase with organic solvents is also one of the effective methods of enzyme modification to improve lipase activity and stability in non-aqueous phase, just as the use of additives, lipid coating, immobilization including covalent attachment and entrapment, and so on [15][16][17][18]. This method is different from the ''solvent engineering'' [19] (organic solvents were used as the reaction medium reported in vast literatures).…”
Section: Introductionmentioning
confidence: 99%